Ligation of uterine vessels in total laparoscopic hysterectomy using Hem-o-lok clips - Jae Eun Lee; Kwang Gi Kim; Dong Ock Lee; Sang Soo Seo; Sokbom Kang; Sang-Yoon Park; Myong Cheol Lim (Elsevier, 2015)
Objective: The Hem-o-lok clip ligation has become the preferred method for vessel ligation. We evaluated the feasibility and safety of uterine vessel ligation using the Hem-o-lok clip during total laparoscopic hysterectomy. Materials and methods: The clinical outcomes of 58 hysterectomies were compared between the following two groups: Hem-o-lok clip group (n = 29) and bipolar coagulation group (n = 29). Results: Of the 29 patients in the Hem-o-lok clip group, bilateral application of Hem-o-lok clips was completed in 25 patients (86%); unilateral use of the bipolar coagulator was needed in four patients for rapid control of bleeding from lacerated uterine vessels during dissection and/or because of anatomical difficulty. No complications, such as dislodgement, slippage, or bleeding, were identified in the Hem-o-lok clip group. No difference was identified in surgical outcomes, such as blood loss or operative time, between the two groups. Postoperative pelvic infections occurred in one patient from each group with unilateral and bilateral use of the Hem-o-lok clip; the ligated uterine vessels using the Hem-o-lok clip were intact, but the coagulated uterine vessels were weakened by the pelvic infections, which caused active uterine bleeding requiring emergent reoperation. Conclusion: The Hem-o-lok clip could be used for ligation of uterine vessels and might be resistant to pelvic infections compared with bipolar coagulation. Prospective randomized trials are needed to confirm the real clinical benefit of this surgical approach.